Computer technology for textiles and apparel - Hu, Jinlian (Oxford ; Philadelphia : Woodhead Pub., 2011)
Computer technology has transformed textiles from their design through to their manufacture. This book reflects the significant advances that have been made in computer technologies, covering a wide range of topics from modeling to electronic textiles and apparel. Part 1 provides a review of different computer based technologies suitable for textile materials. Chapters include computer technology for yarn structure, fabric defects and garment structure. Part 2 discusses modeling and simulation principles of fibers and textiles. Examples of topics include the modeling of yarn and garments. Part 3 concludes with a review of computer based technologies specific to apparel, themes range from 3D body scanning to electronic textiles.
Part 1 Computer-based technology for textile materials: Digital technology for yarn structure and appearance analysis -- Digital-based technology for fabric structure analysis -- Computer vision-based fabric defect analysis and measurement. Part 2 Modelling and simulation of textiles and garments: Key techniques for 3D garment design -- Modelling and simulation of fibrous yarn materials -- Digital technology and modelling for fabric structures -- Modelling ballistic impact on textile materials -- Modelling and simulation techniques for garments. Part 3 Computer-based technology for apparel: Human interaction with computers and its use in the textile apparel industry -- 3D body scanning: generation Y body perception and virtual visualization -- Computer technology from a textile designer's perspective -- Digital printing technology for textiles and apparel -- Approaches to teaching computer-aided design (CAD) to fashion and textiles students -- Three-dimensional (3D) technologies for apparel and textile design -- Integrated digital processes for design and development of apparel.
"The Textile Institute."
Includes bibliographical references and index.
Keywords: Textile industry -- Technological innovations; Clothing trade -- Technological innovations; Textile chemistry -- Technological innovations; Textile fabrics -- Computer simulation; Textile fabrics -- Mathematical models; Textile & fibre technology; TECHNOLOGY & ENGINEERING -- Technical & Manufacturing Industries & Trades; TECHNOLOGY & ENGINEERING -- Textiles & Polymers; Technology; Clothing trade -- Technological innovations; Textile industry -- Technological innovations